The Effect of Career Plan Training on Career Anxiety and Career Self-Efficacy - Elfina, May Lia; Weißmann, Regina (Universitas Islam Tribakti Lirboyo Kediri, 2025)
The unstable economic conditions following the COVID-19 pandemic have highlighted the urgency for young people to better prepare for the increasingly competitive job market. This challenge is particularly pronounced among vocational high school students, who are expected to enter the workforce directly but often lack the career readiness and confidence required to do so. As a result, many experience career anxiety, while low career self-efficacy further hinders their transition into professional life. This study offers a novel contribution by empirically examining the dual effect of structured career plan training on reducing career anxiety and enhancing career self-efficacy among vocational high school students—an intervention rarely studied in this context. The research employed a one-group pretest-posttest experimental design involving 30 students from a vocational high school. Data were analyzed using the Wilcoxon signed-rank test. The results revealed a significant decrease in career anxiety and an increase in career self-efficacy following the intervention (sig < .01). These findings underscore the effectiveness of career plan training as a targeted strategy to strengthen psychological preparedness and decision-making among students facing uncertain career paths. The study recommends that vocational schools incorporate career plan training as part of their student development programs to support smoother transitions into higher education or employment.